Effects of aging on hip abductor-adductor neuromuscular and mechanical performance during the weight transfer phase of lateral protective stepping. (3rd January 2019) - Inacio, Mario; Creath, Rob; Rogers, Mark W.
Abstract: Aging brings about challenges in the ability to recover balance through protective stepping, especially in the lateral direction. Previous work has suggested that lateral protective stepping during weight transfer may be affected by impaired muscle composition and performance of the hip abductors (AB) in older adults. Hence, this study investigated the influence of hip abductor-adductor (AB-AD) neuromuscular performance on the weight transfer phase of lateral protective stepping in younger and older adults. Healthy younger (n = 15) and older adults (n = 15) performed hip AB-AD isometric maximal voluntary contractions (IMVC). Lateral balance perturbations were applied via motorized waist-pulls. Participants were instructed to recover their balance using a single lateral step. Kinetic, kinematic and electromyographic (EMG) data were analyzed during the weight transfer phase. In the hip IMVC task, older adults showed reduced peak AB-AD torque, AB rate of torque development and AB-AD rate of EMG neuromuscular activation (RActv). During the lateral balance perturbations, older individuals had a lower incidence of lateral steps, reduced hip AB-AD RActv and delayed weight transfer. However, several outcomes were larger in the older group, such as, center of mass momentum at step onset, step-side peak rate of vertical force development, hip AB net joint torque, and power. Although older adults had greater hip muscular output during the weight transfer phase, their lateral balance recovery was still impaired. The reduced maximal hip AB-AD capacity, especially RActv, may have been a greater contributor to this impairment, as it affects the ability to generate rapid force, crucial for balance recovery.